The Impact of Trust in Leaders on Organizational Citizenship Behavior of Employees - Gülen Ertosun, Öznur; Istanbul Medipol University (Journal of International Trade, Logistics and Law, 2021)
The positive impact of organizational citizenship behavior on individual and organizational outputs has been studied extensively in recent years. This study aims to examine the importance and impact of trust in leaders on increasing the organizational citizenship behaviors. The population of the study is the while-collar employees of the organized industrial zones (OIZ) of the Marmara region. The data collected with the participation of 320 employees shows us that except for the dimension of sportsmanship; altruism, civil virtue, conscientiousness, and courtesy-based organizational citizenship behaviors are highly correlated with trust in the leader. According to the regression analysis, civil virtue is found to be the organizational behavior dimension most affected by the trust in the leader.